Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The ICPPE initiative: development of default dermal absorption values for use in conjunction with a new global operator exposure model for pesticides - Neil Morgan; Philip Fisher; Marc Kennedy; Felix M. Kluxen; Sabine Martin; Anugrah Shaw; Korinna Wend; Christiane Wiemann (Journal of Consumer Protection and Food Safety, 2026)
The new International Center for Personal Protective Equipment (ICPPE) operator exposure tool, like tools used in Europe and the United States, relies on passive dermal dosimetry exposure data to support risk assessment for the professional use of pesticides via handheld spraying equipment in regions where locally appropriate safety tools have been lacking. The objective of this study was to derive dermal absorption values for use with the tool when substance-specific data are unavailable. Using a database of 680 human in vitro studies covering 23 formulation types and 217 active ingredients, 4 statistical models were applied to derive fixed percentage absorption values for concentrated and diluted pesticide formulations. Furthermore, individual linear dose-absorption equations were generated based on the statistical relationship between applied dose and absorbed dose per µg/cm 2 for the same formulation groups. As fixed percentages of the applied dose, 75th percentile values for concentrated products were 2.2% and 1.2%; for spray dilutions 1.0% and 24%; for solvent-based, water-based and solids 13% and 15%, respectively. Corresponding 95th percentile values for concentrates were 8.3%, 6.0%, and 3.8%; for spray dilutions 58%, 38%; and 41% for solvent-based, water-based and solids, respectively. The resulting fixed percentage defaults provide robust values for conventional use within the ICPPE tool. The alternative dose-based approach incorporates dose-based absorption properties and allows the implementation of the current dataset in future iterations of the risk assessment tool, in alignment with the novel modular dermal exposure prediction model (MODEXMO) concept.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

MODEXMO: A modular non-dietary exposure assessment approach for pesticides using dose-based dermal absorption prediction - Felix M. Kluxen; Korinna Wend; Christiane Wiemann; Edgars Felkers; Neil Morgan (Regulatory Toxicology and Pharmacology, 2026)

Development of a High-throughput Morphological Assay for Evaluating Mesenchymal Stromal Cell-derived Extracellular Vesicle Modulation of Brain Pericyte Secretory Phenotype - Courtney E. Campagna; Andrew M. Larey; Kanupriya R. Daga; Morgan Roos; Sneha Ghosh; Neil Grimsey; Jin Han; Ross A. Marklein (Stem Cell Reviews and Reports, 2025)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are a promising therapeutic tool for treating many neurodegenerative diseases. Neuroinflammation plays a major role in many of these conditions through an orchestration of interdependent processes that lead to the breakdown of the blood-brain barrier (BBB), infiltration of immune cells and neuronal death. MSC-EVs have shown preliminary evidence of modulating neuroinflammation, but their mechanisms of action are still unknown. Therefore, we explored the potential of MSC-EVs in modulating brain pericytes, a cell type that plays a critical role in BBB maintenance but has not been investigated as a therapeutic target for MSC-EVs. Brain pericytes are multifaceted cells that can modulate neuroinflammation through their involvement in BBB homeostasis, as well as the innate and adaptive immune response. Pericyte morphology has been shown to change in response to inflammatory stimuli in vivo, hence, we used this behavior to develop a quantitative morphological profiling approach to assess the immunomodulatory function of MSC-EVs in a high-throughput, low-cost manner. Using this assay, we were able to demonstrate that MSC-EVs manufactured under various conditions (2D, 3D, and in response to cytokine priming) could induce distinct pericyte morphological responses indicative of changes in secretion of chemokines and cytokines relevant to neuroinflammation.

Status of Florida’s pillar coral population: in situ declines and ex situ successes - Karen L. Neely; Rachel M. Morgan; Keri L. O’Neil; Nikkie Cox; David S. Gilliam; Michelle B. Mair; Brian K. Walker; Amanda Zummo; Cailin Harrell; Ananda Ellis (Frontiers in Marine Science, 2025)
The population of pillar coral, Dendrogyra cylindrus , in Florida was decimated from 2013 to 2020, primarily by the emergence of stony coral tissue loss disease (SCTLD). Monitoring of survivors from 2021 to early 2025 showed that the population underwent an additional 96% decline in live tissue, a 78% loss in living colonies, and a 55% loss of genotypes. SCTLD continued to be the primary cause of these losses. Although some surviving tissue isolates exhibited small amounts of growth, the population remains extremely small, with only an estimated 9.6 m 2 of tissue remaining on 23 colonies (15 genotypes). Additionally, the colonies are far too dispersed to successfully fertilize spawned gametes. Further declines in the population since 2020 highlight the instability of the remnant population and underscore the value of the pillar coral rescue program and ongoing propagation efforts. As of February 2025, eight different in situ and ex situ facilities were caring for rescued D. cylindrus . Experimental fragmentation at one in situ nursery identified variable, but continually improving, growth rates across multiple fragmentation events. Sexual propagation efforts at an ex situ nursery documented 105 different rescue fragments spawning over 5 years. The smallest fragment was 9 cm × 7 cm × 9 cm, suggesting a potential “minimum colony size” for this species to have reproductive capacity. During these spawning events, 82 juveniles were being raised ex situ in early 2025. Two of these sexually propagated juveniles spawned 6 years after settlement, thus establishing a potential minimum age for reproduction.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Data collection initiatives of the crop protection industry – A mission to improve non-dietary risk assessment in Europe - Neil Morgan; Sarah Adham; Edgars Felkers; Felix M. Kluxen; Christian J. Kuster; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Proposals for new spray drift exposure values in orchards and vineyards for residents and bystanders - Udo Blaschke; Edgars Felkers; Nicola J. Hewitt; Felix M. Kluxen; Neil Morgan; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Proposals for new transfer coefficient (TC) values for worker re-entry activities in grape vineyards - Udo Blaschke; Edgars Felkers; Nicola J. Hewitt; Felix M. Kluxen; Neil Morgan; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Efficiency of working coveralls and chemical resistant gloves in reducing operator exposure to pesticides - Christian J. Kuster; Felix M. Kluxen; Edgars Felkers; Neil Morgan; Nicola J. Hewitt; Julien Durand-Reville (Journal of Consumer Protection and Food Safety, 2024)
Personal Protective Equipment (PPE) is used to reduce exposure when working with chemicals. For pesticides, exposure scenarios comprise mixing and loading (M&L) and application. The exposure prediction model recommended by European regulatory agencies for operator risk assessments—the Agricultural Operator Exposure Model (AOEM) – is based on 48 operator exposure studies involving over 500 professional operators from 10 European countries in typical working situations to assess exposure under realistic field conditions. We used the AOEM data to assess the efficiency of exposure reduction resulting from wearing chemical-resistant nitrile gloves and non-certified working coveralls during M&L (tank and backpack sprayer), applications using groundboom and airblast spraying, and outdoor and indoor (greenhouse) applications using handheld sprayers. All studies indicated consistent and high exposure reduction > 90% for gloves and non-certified coveralls across all investigated scenarios. Exceptions were almost exclusively observed when an operator incorrectly used the PPE. The mean exposure reduction from all operators, including those that used PPE incorrectly, was 95.0% for gloves and 96.4% for polyester/cotton working coveralls during M&L, and 91.1% for gloves and 94.9% for non-certified coveralls during all application scenarios. This analysis confirms the essential role of PPE and non-certified working coveralls in reducing operator exposure to pesticides. Outliers indicate that operators need to be properly trained and adhere to label instructions to apply pesticides according to good agricultural practices.

Minimizing operator exposure: field data analysis of three closed transfer systems for pesticide mixing and loading - Juan Sasturain; Udo Blaschke; Franz Stauber; Tirso Oteyza; Jean-Pierre Huby; Sarah Adham; Neil Morgan; Anne-Kim Vinck; Michal Kicinski; Nicola J. Hewitt; Christian J. Kuster (Journal of Consumer Protection and Food Safety, 2024)
Three Closed Transfer Systems (CTS) were evaluated for their reduction of operator exposure to plant protection products during mixing and loading: the inverted extraction systems, easyFlow M and easyconnect, and the probe extraction system, GoatThroat ® . Exposure data were generated for gloves, hands, head, inner and outer body dosimeters generated in 4 European countries for high rate (Sorbitol) and low rate (Xylitol) surrogate products used by 12 operators. Exposure values were compared with predicted data using the Agricultural Operator Exposure Model as a benchmark for open pour loading (used in the EFSA Guidance). The CTS types conformed with the ISO 21191 standard for CTS performance, and their potential to significantly reduce operator exposure was confirmed in this study. There was no statistical difference in potential (naked) or actual (one layer of clothing) operator exposure using both inverted CTS types; allowing these data to be pooled. The inverted CTS types resulted in higher mean protection (> 98% potential exposure and > 95% actual exposure) than GoatThroat ® (> 80% potential exposure and > 95% actual exposure). These data can be used to derive reduction factors that could be used in the AOEM model for calculations involving mitigation e.g., 0.05 for inverted CTS since they reduced exposure by > 95% and 0.3 for probe extraction CTS types. All 3 CTS significantly reduced operator exposure to products during M&L. These and future CTS types which comply with ISO 21191 standards could be considered as mitigation devices. These findings will help to build confidence of farmers to use CTS routinely, resulting in safer pesticide handling.

Investigating the perceived versus actual gastrointestinal nematode challenge on extensive sheep farms - Eilidh Geddes; Claire Morgan-Davies; Ann McLaren; Philip J. Skuce; Jade M. Duncan; Neil Sargison; Fiona Kenyon (Veterinary Parasitology, 2024)

Use of guinea pig data to obtain starting points for skin sensitisation risk assessment - A commentary - David Basketter; Namali Corea; Marco Corvaro; Arthur Grivel; Felix M. Kluxen; Neil Morgan; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

A comparison between field measurements of vapour concentrations of plant protection products and predictions by the BROWSE model - M. Clare Butler Ellis; Edgars Felkers; Sarah Adham; Anne-Kim Vinck; Kathrin Bürling; Neil Morgan (Regulatory Toxicology and Pharmacology, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Assessing the risk of induction of skin sensitization to plant protection products: A quantitative approach - Namali Corea; Marco Corvaro; Felix M. Kluxen; Arthur Grivel; Neil Morgan; Christiane Wiemann; David Basketter (Regulatory Toxicology and Pharmacology, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Genomic, transcriptomic, and protein landscape profile of CFTR and cystic fibrosis - Morgan Sanders; James M. J. Lawlor; Xiaopeng Li; John N. Schuen; Susan L. Millard; Xi Zhang; Leah Buck; Bethany Grysko; Katie L. Uhl; David Hinds; Cynthia L. Stenger; Michele Morris; et al. (Human Genetics, 2021)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The Length Versus Diameter Relationship and Radial Force Properties of the Amplatzer™ Vascular Plug Type IV: Observations for Oversizing - Jenny E. Zablah; Rachel Fry; Derek Eilers; Gareth Morgan; Neil Wilson; Michael Ross (Cardiovascular Engineering and Technology, 2019)

Nutrients from salmon parents alter selection pressures on their offspring - Sonya K. Auer; Graeme J. Anderson; Simon McKelvey; Ronald D. Bassar; Darryl McLennan; John D. Armstrong; Keith H. Nislow; Helen K. Downie; Lynn McKelvey; Thomas A.J. Morgan; Karine Salin; Danielle L. Orrell; et al. (Ecology Letters, 2018)
Organisms can modify their surrounding environment, but whether these changes are large enough to feed back and alter their evolutionary trajectories is not well understood, particularly in wild populations. Here we show that nutrient pulses from decomposing Atlantic salmon ( Salmo salar ) parents alter selection pressures on their offspring with important consequences for their phenotypic and genetic diversity. We found a strong survival advantage to larger eggs and faster juvenile metabolic rates in streams lacking carcasses but not in streams containing this parental nutrient input. Differences in selection intensities led to significant phenotypic divergence in these two traits among stream types. Stronger selection in streams with low parental nutrient input also decreased the number of surviving families compared to streams with high parental nutrient levels. Observed effects of parent‐derived nutrients on selection pressures provide experimental evidence for key components of eco‐evolutionary feedbacks in wild populations.

Applying species distribution modelling to a data poor, pelagic fish complex: the ocean sunfishes - Natasha D. Phillips; Neil Reid; Tierney Thys; Chris Harrod; Nicholas L. Payne; Cheryl A. Morgan; Hannah J. White; Siobhán Porter; Jonathan D.R. Houghton (Journal of Biogeography, 2017)
Aim Conservation management of vulnerable species requires detailed knowledge of their spatial and temporal distribution patterns. Within this context, species distribution modelling ( SDM ) can provide insights into the spatial ecology of rarely encountered species and is used here to explore the distribution pattern of ocean sunfishes ( Mola mola and M. ramsayi ). Both species are prone to high levels of bycatch and are classified respectively as Globally Vulnerable and Not Assessed by the IUCN ; although their overall range and drivers of distribution remain poorly defined. Here, we constructed suitable habitat models for Mola spp. on a global scale and considered how these change seasonally to provide a much needed baseline for future management. Location Global. Methods Sighting records collected between 2000 and 2015 were used to build SDM s and provided the first global overview of sunfish seasonal distribution. Post hoc analyses provided a quantitative assessment of seasonal changes in total range extent and latitudinal shifts in suitable habitat. Results Mola is a widely distributed genus; however, sightings exhibited significant spatial clustering most notably in coastal regions. SDM s suggested that Mola presence was strongly dependent on sea surface temperatures with highest probability of presence between 16 and 23°C. The models identified significant variation in seasonal range extent with latitudinal shifts throughout the year; although large areas of suitable year‐round habitat exist globally. Main conclusions We provided the first assessment of Mola distribution on a global scale, with evidence of a wide latitudinal range and significant clustering in localized “hotspots” (notably between 40–50°N). By assessing the results of SDM s alongside evidence from published satellite tagging studies, we suggest that the species within the genus Mola are highly mobile, acting as facultative seasonal migrants. By identifying key suitable habitat alongside potential movement paths, this study provides a baseline that can be used in active conservation management of the genus.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

A role for STEAP2 in prostate cancer progression - Helen Whiteland; Samantha Spencer-Harty; Claire Morgan; Howard Kynaston; David Hywel Thomas; Pradeep Bose; Neil Fenn; Paul Lewis; Spencer Jenkins; Shareen H. Doak (Clinical & Experimental Metastasis, 2014)

An Ecology of Prestige in New York City: Examining the Relationships Among Population Density, Socio-economic Status, Group Identity, and Residential Canopy Cover - J. Morgan Grove; Dexter H. Locke; Jarlath P. M. O’Neil-Dunne (Environmental Management, 2014)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Challenges to Educating the Next Generation of Wildland Fire Professionals in the United States - Leda N. Kobziar; Monique E. Rocca; Christopher A. Dicus; Chad Hoffman; Neil Sugihara; Andrea E. Thode; J. Morgan Varner; Penelope Morgan (Journal of Forestry, 2009)
Over the last 20 years, the duties of US fire professionals have become more complex and risk laden because of fuel load accumulation, climate change, and the increasing wildland-urban interface. Incorporation of fire use and ecological principles into fire management policies has further expanded the range of expertise and knowledge required of fire professionals. The educational and training systems that produce these professionals, however, have been slow to organize an updated and coordinated approach to preparing future practitioners. Consequently, aspiring fire professionals face numerous challenges related to scheduling conflicts, limited higher education programs in fire science, lack of coordination between fire training and higher education entities, and the overall difficulty of obtaining education and training without sacrificing experience. Here, we address these and other challenges with potential solutions and outline the first steps toward their implementation. We organize the necessary aspects of professional fire preparation into a representative model: a fire professional development triangle comprised of education, training, and experience. For each of these aspects, we suggest changes that can be made by employers, educators, and nongovernmental organizations to provide a more streamlined mechanism for preparing the next generation of wildland fire professionals in the United States.

Predicting Opportunities for Greening and Patterns of Vegetation on Private Urban Lands - Austin R. Troy; J. Morgan Grove; Jarlath P. M. O’Neil-Dunne; Steward T. A. Pickett; Mary L. Cadenasso (Environmental Management, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

Species Recognition from Postpharyngeal Gland Contents of Ants of the Cataglyphis bicolor Group - Neil J. Oldham; E. David Morgan; Donat Agosti; Rudiger Wehner (Journal of Chemical Ecology, 1999)